2020
DOI: 10.1039/d0ra07062a
|View full text |Cite
|
Sign up to set email alerts
|

Several coumarin derivatives and their Pd(ii) complexes as potential inhibitors of the main protease of SARS-CoV-2, anin silicoapproach

Abstract: Coumarin derivatives and their Pd(ii)-complexes have shown a higher binding potential towards SARS-CoV-2 Mpro than chloroquine/cinanserin along with lower toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 60 publications
0
26
0
1
Order By: Relevance
“…The formation of the complex is facilitated by the unfavorable donor-donor interaction, which occurs between the hydrogen proton of the substituted amino group of the pyrrolo( Mohapatra et al, 2020b , Mohapatra et al, 2020a , Mohapatra et al, 2020b , Mohapatra et al, 2020 , Mohapatra et al, 2020 , Lipsitch et al, 2020 , Mohapatra and Rahman, 2020 , Almendros, 2020 , Tiwari et al, 2020 , Ramteke et al, 2019 , Saadat et al, 2020 , Baildya et al, 2020 , Milenkovic et al, 2020 , Cardoso and Mendanha, 2021 , Kodchakorn et al, 2020 , Sahu et al, 2020 , Jin et al, 2020 , GaussView 6.0, (Gaussian Inc., Wallingford, CT, USA), 2019 , Becke, 1993 , Frisch, 2009 , Mahapatra et al, 2013 , Sarangi et al, 2020 , El-ajaily et al, 2019 , Yousef et al, 2012 , Yousef et al, 2013 , Govindarajan et al, 2012 , Pearson, 1989 , Padmanabhan et al, 2007 , Alam et al, 2019 , Jans and Wagstaff, 2020 , Al-Tawfiq et al, 2020 , Monforte et al, 2020 , Amin et al, 2020 , Daina et al, 2017 , El-Saadi et al, 2015 Dec , http://www.swissadme.ch/ (as accessed on 30th Oct., 2020 , Lipinski et al, 2001 , Veber et al, 2002 , https://www.3ds.com/products-services/biovia/products/molecular-modeling-simulation/biovia-discovery-studio/ (as accessed on 30th Oct., 2020 )( Mohapatra et al, 2020a , Mohapatra et al, 2020b , Mohapatra and Rahman, 2020 )triazin cycle with the residue of amino acid Thr26. The π-H π-Sulphur interaction takes place between the pyrrolo( Mohapatra et al, 2020b , Mohapatra et al, 2020a , Mohapatra et al, 2020b , Mohapatra et al, 2020 , Mohapatra et al, 2020 , Lipsitch et al, 2020 , Mohapatra and Rahman, 2020 , …”
Section: Results Of the Docking Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of the complex is facilitated by the unfavorable donor-donor interaction, which occurs between the hydrogen proton of the substituted amino group of the pyrrolo( Mohapatra et al, 2020b , Mohapatra et al, 2020a , Mohapatra et al, 2020b , Mohapatra et al, 2020 , Mohapatra et al, 2020 , Lipsitch et al, 2020 , Mohapatra and Rahman, 2020 , Almendros, 2020 , Tiwari et al, 2020 , Ramteke et al, 2019 , Saadat et al, 2020 , Baildya et al, 2020 , Milenkovic et al, 2020 , Cardoso and Mendanha, 2021 , Kodchakorn et al, 2020 , Sahu et al, 2020 , Jin et al, 2020 , GaussView 6.0, (Gaussian Inc., Wallingford, CT, USA), 2019 , Becke, 1993 , Frisch, 2009 , Mahapatra et al, 2013 , Sarangi et al, 2020 , El-ajaily et al, 2019 , Yousef et al, 2012 , Yousef et al, 2013 , Govindarajan et al, 2012 , Pearson, 1989 , Padmanabhan et al, 2007 , Alam et al, 2019 , Jans and Wagstaff, 2020 , Al-Tawfiq et al, 2020 , Monforte et al, 2020 , Amin et al, 2020 , Daina et al, 2017 , El-Saadi et al, 2015 Dec , http://www.swissadme.ch/ (as accessed on 30th Oct., 2020 , Lipinski et al, 2001 , Veber et al, 2002 , https://www.3ds.com/products-services/biovia/products/molecular-modeling-simulation/biovia-discovery-studio/ (as accessed on 30th Oct., 2020 )( Mohapatra et al, 2020a , Mohapatra et al, 2020b , Mohapatra and Rahman, 2020 )triazin cycle with the residue of amino acid Thr26. The π-H π-Sulphur interaction takes place between the pyrrolo( Mohapatra et al, 2020b , Mohapatra et al, 2020a , Mohapatra et al, 2020b , Mohapatra et al, 2020 , Mohapatra et al, 2020 , Lipsitch et al, 2020 , Mohapatra and Rahman, 2020 , …”
Section: Results Of the Docking Studymentioning
confidence: 99%
“…The medical waste management would soon emerge as a big challenge before the governments in the wake of the rapid transmission of the disease, and the large scale use of masks and other accessories thereof. As there is no efficient approved treatment or drugs, the computational strategy is a promising way and plays a significant role in pharmaceutical industries to bring new drugs ( Baildya et al, 2020 , Mohapatra et al, 2020 , Milenkovic et al, 2020 , Cardoso and Mendanha, 2021 , Kodchakorn et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A hybrid of phenylsulfonylfuroxan and coumarin induced caspase-dependent cell death, autophagy, and suppressed PI3K/Akt/mTOR signaling pathway to kill cancer cells [176][177][178]. Accordingly, it has been suggested that coumarin might protect against COVID-19 by blocking the protease enzyme of SARS-CoV-2 [179,180].…”
Section: Coumarinmentioning
confidence: 99%
“…The Coronavirus disease 2019 (COVID-19) caused by Severe Acute Respiratory Syndrome virus 2 (SARS-CoV-2) is a viral, respiratory lung disease [ 1 ]. The spread of COVID-19 has been rapid, and it has affected the daily lives of millions across the globe.…”
Section: Introductionmentioning
confidence: 99%